The influence of diversity in learning strategies and various motivations for conceptual understanding - Nasrun Budi Utomo (Journal of diversity in learning (JDIL), 2021)
The purpose of this research is to see: 1) Knowing the mathematics learning outcomes of integer material with a direct learning model and using problem-based learning strategies. 2) the influence of the influence of mathematics learning outcomes with high and low motivation which is treated using problem-based learning models and direct learning. 3) The interaction between the problem-based learning model and the direct learning model, as well as students' learning motivation towards the mathematics learning outcomes of integer material. This research is a quantitative study by determining the sample using random sampling technique. This research is a quantitative study by determining the sample using random sampling technique. The number of samples for the control class was 52 students and the experimental class was 52 students, so the sample size was 104 students. Data collection was carried out using test questions and motivation questionnaires, with testing using the 2-way ANOVA test statistic. Retrieval of data using test questions and motivation questionnaires, using the 2-line ANOVA statistical test. The results of the study are as follows: 1) There is an influence on the results of learning mathematics using the Problem Based Learning model and direct learning model. 2) There is an effect of mathematics learning outcomes of seventh grade junior high school students between groups of students who have high learning motivation and low learning motivation. 3) The interaction between the Problem Based Learning model and the direct learning model with students' learning motivation towards Mathematics learning outcomes.